Implementation of Social-Emotional Learning in Fostering Positive Character in Children at Taruna Kindergarten - Astuti; Rostianingsih; Syahru Ramadhan (Eduscape : Journal of Education Insight, 2026)
This study was motivated by the need at Taruna Kindergarten in Bima City to strengthen positive character traits in young children through targeted and sustained social-emotional learning. Initial observations indicated that some children still struggled with managing their emotions, showing empathy, cooperating, and communicating positively. This study aims to describe the process of implementing social-emotional learning and its impact on children’s character development. The method used is qualitative descriptive research, as this approach is most appropriate for deeply describing learning phenomena that occur naturally without manipulating variables, and allows the researcher to uncover the meaning of children’s social-emotional behaviors based on real-world classroom contexts. Data collection techniques included direct observation of learning activities, in-depth interviews with teachers and the school principal, and documentation in the form of activity photos, teacher notes, and child development monitoring instruments. The data were analyzed using the Miles and Huberman interactive analysis model, which involves data reduction, data presentation, and continuous conclusion drawing. The research findings indicate that, based on interviews, observations, and field notes, several key strategies implemented by teachers at TKTaruna—namely, encouraging greetings, friendly interactions, and smiling—have been shown to improve polite behavior. morning circle activities help regulate children’s emotions; observations show that children are able to express their feelings, and the quiet corner effectively soothes emotions; engaging in group work activities to foster cooperation is evident from the interaction in sharing tasks during class projects. There is a reinforcement of appreciation to encourage positive behavior; teachers’ notes indicate an increase in children’s participation following praise. The findings in this study confirm that social-emotional learning contributes significantly to the sustained development of positive character in children.